2021
DOI: 10.3390/ma14051281
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Shielding Properties of Knitted Fabric Made from Polyamide Threads Coated with Silver

Abstract: This paper investigates a textile material of low surface mass for its protection against electromagnetic radiation (EMR), which is suitable for composite structures of garments, and for technical and interior applications. The shielding effectiveness against EMR of fabric knitted from polyamide threads coated with silver, measured in the frequency range of 0.9 GHz to 2.4 GHz, indicated a high degree of protection. The key contribution of the paper is the evaluation of the stability of the shielding properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Furthermore, when comparing the surface resistivity (Figure 3) with the volume resistivity (Figure 5) for each fabric fiber composition and each knit pattern case, it can be seen that the volume resistivity is slightly higher than the surface resistivity, supposedly due to the presence of air in the fabric pores that act as an insulator. 26…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, when comparing the surface resistivity (Figure 3) with the volume resistivity (Figure 5) for each fabric fiber composition and each knit pattern case, it can be seen that the volume resistivity is slightly higher than the surface resistivity, supposedly due to the presence of air in the fabric pores that act as an insulator. 26…”
Section: Resultsmentioning
confidence: 99%
“…The loss of SE due to wet cleaning was more obvious than dry cleaning in this case. At a frequency of 2.4 GHz, better preservation of SE was observed for dry cleaning than for water washing (Figure 10o) [273].…”
Section: Washing Stressesmentioning
confidence: 98%
“…(o) Shielding efficiency of the silver-coated polyamide yarn upon dry and wet cleaning at 0.9 GHz (i) and 2.4 GHz (ii). Reproduced with permission[273] Copyright 2021, MDPI.…”
mentioning
confidence: 99%
“…The scanning electron microscope examination of the surface revealed that the silver coating on the polyamide yarn had been peeled. The level of degradation of the functional silver coating after wet washing was higher than after dry cleaning [ 15 ].…”
Section: Introductionmentioning
confidence: 99%